حجج البلاغيين في البنية التصويرية للتشبيه البليغ - دومي, أحمد; يحي, شعيب (جامعة الوادي - University of Eloued, 2021)
يتحدَّثُ هذا البحث عن إحدى الإشكاليات التي شَهِدَتها البلاغة العربية، وتتمثَّلُ في الصورة التي حُذفت منها الأداة والوجه، فقد رأى بعضُ البلاغيين أنها تشبيه، في حين رأى آخرون جواز كونها استعارة، وطالت مناقشاتهم حول هذه القضية، وكان لكل فريق تحليله البلاغي الذي يرتضيه ويراه صوابا، فسار البحث بحَذَرٍ في تجلية هذا الجانب من البلاغة العربية، مبيّنا سبب الخلاف، ومُنتهِجًا في تحقيق ذلك المنهج الوصفي التحليلي. Abstract: The article talks about a problem known to Arab rhetoric, which is the Figure of speech from which the tool of similarity was removed and also the common meaning between the two parties is deleted, and some saw it as analogy. Others saw it as a metaphor. Their discussion has been long. This research came to explain the case and shows the cause of the dispute. He went on an analytical descriptive approach.
مقال
Keywords: الحجاج، التشبيه، الاستعارة، الاختلاف، البنية، البلاغة